Potential Use of Natural Zeolite and Green Shells in Biodiesel Production - Siswanto*, Anggun Puspitarini; Damayani, Intan Ardina (Graduate School of Universitas Syiah Kuala, 2023)
As energy needs continue to rise in line with the use of fossil energy, which is difficult to renew, other alternative energy is needed to continue to meet current and future energy needs. One alternative energy that is easy to produce is biodiesel. One of the raw materials that is quite widely used and developed in making biodiesel is waste cooking oil. According to statistical data, Indonesia can produce waste cooking oil of 5.06 tons per year. Waste cooking oil contains free fatty acids that can be processed into biodiesel using the help of heterogeneous catalysts. One source of heterogeneous catalysts that can be used is CaO, which can be found in green shells, where the CaO contained can be taken through the calcination process of green shells. To maximize the waste cooking oil processing process, an adsorption pretreatment process can be carried out. The adsorption process is carried out to reduce the FFA levels and acid numbers contained in waste cooking oil so that the transesterification reaction process can run optimally. Natural zeolite can be used as a good adsorbent to purify and lower the acid number of waste cooking oil. This study aims to find the best operating conditions in producing biodiesel made from waste cooking oil with a pretreatment adsorption process using natural zeolite and green shell catalyst through the factorial design method, where from the results of the research carried out, it was found that the density and viscosity met the SNI, the biodiesel yield produced was 45-65% and the cetane number test on samples 3 and 7 was 34,7 and 34,2 which did not meet the SNI. The operating temperature and amount of catalyst used in the biodiesel manufacturing process produce biodiesel with good density, viscosity, and yield, namely at a temperature of 60C and a catalyst content of 6 grams. The operating temperature of 65C produces a smaller density because the boiling point of alcohol is 64.7C, so the reaction process is not perfect.